Death penalty under hudud and qisas from modern penology's perspective - Candra, Marli (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
Death punishment is a debatable issue that attracts the attention of scholars either in favour of or against it. This issue is intensively discussed in countries which still retain the death punishment for the offence committed in their territory, like the United State of America (USA), China and most of Muslim countries. In the case of the USA and China, the death punishment comes into the issue of crime prevention and reduction, whereas in Muslim countries, death punishment relates to the issue associated to religion as the death punishment is mostly related to ḥudud and qiṣaṣ offenses which are unchangeable and should be applied in the Muslim life. This research tries to elucidate the penological aspect of death punishment in Islamic criminal law and compares it to the modern penological policy of modern criminal law. It is mostly based on qualitative approach which was designed to gather an in-depth understanding of the concept of punishment and its justification in the modern penology as well as in Islamic perspective. This approach is also based on analytical as well as comparative analysis in order to find the answers to the questions in this research. It is found that the justification for death punishment which is mainly contained in the ḥudud and qiṣaṣ offenses is not detrimental to what is understood by modern penology. Islamic law provides death punishment for serious offenses, but it also prescribes ways on how to abolish such punishments. It is in concurrence with the modern abolishment approach with regard to death punishment. In another dimension, it is concluded that Islamic law is in accordance with the concept of human rights, particularly in the matter of punishment. Therefore, it is applicable to our modern era.